2018
DOI: 10.1504/ijrapidm.2018.10010829
|View full text |Cite
|
Sign up to set email alerts
|

Thingiverse: review and analysis of available files

Abstract: Visit www.inderscience.com for details of over 380 titles

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Meanwhile, the patient's medical record files were taken using systematic sampling [9]. The research variables observed were the average patient visit, the average thickness of the medical record file, the number of medical record file storage shelfs, the size of the medical record file storage shelf and the shrinkage of medical records [10].…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, the patient's medical record files were taken using systematic sampling [9]. The research variables observed were the average patient visit, the average thickness of the medical record file, the number of medical record file storage shelfs, the size of the medical record file storage shelf and the shrinkage of medical records [10].…”
Section: Methodsmentioning
confidence: 99%
“…These CAD data lakes have since become an emergent area for research with researchers investigating the open source nature of design and ability to share knowledge, as well as the barriers in the application of stored 3D models due to the variety in geometric representations used (e.g. .stl, .ipt, .iges, .f3d) (Buehler et al, 2015;Baumann and Roller, 2018;Alcock et al, 2016). Given the wealth of available models for individuals to download, the challenge that this paper identifies lies in search and retrieval.…”
Section: Introductionmentioning
confidence: 99%